Challenges and Opportunities for Strengthening Bottom‐Tow Fisheries Sustainability - Suresh A. Sethi; Robert D. Murphy; Matthew R. Baker; Anita C. Kroska; Haraldur A. Einarsson; Owen S. Hamel; Shelton J. Harley; Pingguo He; James Ianelli; Stan Kotwicki; Robert A. McConnaughey; Chris McGonigle; et al. (Fish and Fisheries, 2026)
Bottom‐tow gear fisheries (trawls and dredges) produce ~24 million mt of harvest annually, representing a globally important animal‐sourced food system. While many are currently sustainably managed, growing concern over the potential for ecosystem impacts from bottom‐tow gears has increased pressure to improve these fisheries. We assembled an international working group of > 30 contributors, including fishing industry participants, managers, non‐governmental ocean conservation organization representatives, and scientists to synthesize obstacles to bottom‐tow fisheries sustainability and to develop expert‐based recommendations to operationalize sustainability advancements moving forward. We identified 30 key gaps impeding bottom‐towed fisheries sustainability spanning 6 core challenge areas including: seafloor disturbance, bycatch and discards, management design and implementation, fishing operations, cross‐sector conflicts, and public perception and communication. We generated 28 priority recommendations to address bottom‐tow fisheries sustainability obstacles with themes including: addressing data gaps, advancing mechanistic understanding and modelling tools, strengthening management processes, and improving knowledge sharing and communication. Cross‐disciplinary and diverse system experience among fisheries and marine ecosystem stakeholders will be critical for operationalizing bottom‐tow fisheries sustainability advancements. As the global human population approaches 10 bn in the next 30 years, ensuring sustainable wild capture fisheries is an imperative for feeding the world. Outputs from this synthesis serve as a resource for fishing and marine ecosystem stakeholders to identify key challenge areas and associated entry points for solutions‐oriented efforts to improve the sustainability of bottom‐tow fisheries.

Evaluating the performance of selected CMIP6 GCMs for simulations of historical temperature over Ethiopia - Alehegn Belay Tagele; Temesgen Gashaw Tarkegn; Pieter R. van Oel; Ram Lakhan Ray; Gebrekidan Worku Tefera; Sintayehu Fetene Demessie; Alemayehu Abate Shawul; Othoo Calvince Ouko; Daniel Berhanu; Amare Haileslassie; Abeyou W. Worqlul; Amare Bantider; et al. (Theoretical and Applied Climatology, 2026)
This study evaluates the performance of seven Global Climate Models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and their Ensemble mean in reproducing historical maximum (Tmax) and minimum (Tmin) temperatures across five agro-ecological zones (AEZs) of Ethiopia during 1995–2014. The assessment covers daily to annual time scales using observational and GCM datasets. Model performance was evaluated using Percent Bias (PBIAS), Root Mean Square Error (RMSE), and correlation coefficient (r), while the Comprehensive Rating Index (CRI) was applied for ranking. Results show substantial spatial and temporal variability in model performance. For Tmax, the Ensemble mean and EC-Earth3-veg performed best at the daily scale, while EC-Earth3-veg, MPI-ESM1-2-LR and BCC-CSM2-MR excelled at the monthly scale across most AEZs. Seasonally, top-performing models included Ensemble mean, MPI-ESM1-2-LR and MRI-ESM2-0 during Bega (October-January), EC-Earth3-veg, CNRM-CM6-1 and Ensemble mean during Belg (February-May) and CNRM-CM6-1 and MPI-ESM1-2-LR during Kiremt (June-September). For Tmin, CNRM-CM6-1, BCC-CSM2-MR and Ensemble mean ranked highest at both daily and monthly scales in most AEZs. At the annual scale, MRI-ESM2-0, Ensemble mean, MPI-ESM1-2-LR and CNRM-CM6-1 excel for Tmax, while EC-Earth3-veg, BCC-CSM2-MR and Ensemble mean lead for Tmin across most AEZs. MIROC6 consistently exhibited the weakest performance for both Tmax and Tmin across most AEZs and time periods. Thus, the Ensemble mean of all evaluated models does not consistently rank among the top three performers across all AEZs and time scales. The identified best-performing CMIP6 models provide valuable tools for assessing climate change impacts and developing region-and time-specific adaptation strategies in Ethiopia. Given the variability in GCM performance across AEZs and time scales, national or large-scale studies would benefit from using the Ensemble mean derived from the best-performing models. This study provides crucial insights into the strengths and weaknesses of different GCMs, supporting evidence-based decision-making and enhancing efforts to build climate resilience and adaptation strategies in the region.

Correction: Modeling impacts of climate change on blue and green water, and crop yield using SWAT + in lake Tana sub-basin (Ethiopia) - Temesgen Gashaw Tarkegn; Pieter R. van Oel; Abebe D. Chukalla; Ram Lakhan Ray; Gebrekidan Worku Tefera; Abeyou W. Worqlul; Yihun T. Dile; Amare Haileslassie; Enyew Adgo; Amare Bantider; Meron Teferi Taye (Modeling Earth Systems and Environment, 2026)

Modeling impacts of climate change on blue and green water, and crop yield using SWAT + in Lake Tana sub-basin (Ethiopia) - Temesgen Gashaw Tarkegn; Pieter R. van Oel; Abebe D. Chukalla; Ram Lakhan Ray; Gebrekidan Worku Tefera; Abeyou W. Worqlul; Yihun T. Dile; Amare Haileslassie; Enyew Adgo; Amare Bantider; Meron Teferi Taye (Modeling Earth Systems and Environment, 2026)

Complex Love Numbers in the Diurnal and Semidiurnal Tidal Bands Determined from Satellite Tracking and Altimetry - R. D. Ray; B. D. Loomis; K. E. Rachlin; J. J. Otero Torres (Pure and Applied Geophysics, 2026)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Multiple anthelmintic drug resistance in the canine hookworm Ancylostoma caninum: AAVP position paper and research needs - Timothy G. Geary; Jason Drake; John S. Gilleard; Jeba R.J.Jesudoss Chelladurai; Pablo D. Jimenez Castro; Ray M. Kaplan; Antoinette E. Marsh; Craig R. Reinemeyer; Guilherme G. Verocai (Veterinary Parasitology, 2025)

A framework for sustainable urban settlement planning: Integrating geographic information system and multi-criteria decision analysis - S. K. Ray; A. Teja; S. Chaudhary; M. H. Kumar; R. Rahul; K. Rammohan; D. Himabindu (Environment, Development and Sustainability, 2025)

Reduced Cerebellar Volumes Associate with P300 Amplitude Attenuation in Children with Clinical High Risk for Psychosis and Early Onset Psychosis - Hanne van der Heijden; Hesham M. Hamoda; Aliza Ray; Maria Goldman; Maya Golden; Kelsey Graber; Frank H. Duffy; Eugene D’Angelo; Borjan Gagoski; Merve Koç Yekedüz; Carter R. Petty; Jaymin Upadhyay; et al. (The Cerebellum, 2025)

Performances of reanalysis products in representing the temperature climatology of Ethiopia - Tazebew Abera Tadesse; Temesgen Gashaw Tarkegn; Ram Lakhan Ray; Gebrekidan Worku Tefera; Sintayehu Fetene Demessie; Alemayehu Abate Shawul; Abeyou W. Worqlul; Pieter R. van Oel; Yihun T. Dile; Abebe D. Chukalla; Amare Haileslassie; Endeg Aniley; et al. (Theoretical and Applied Climatology, 2025)

Genomic affinity following restoration of a locally extirpated species: a case study of desert bighorn sheep in Texas - Emily A. Wright; Joseph D. Manthey; Michael R. Buchalski; Bonnie R. McKinney; David A. Ray; Caleb D. Phillips; Robert D. Bradley (Conservation Genetics, 2024)

Identification of QTLs for symbiotic nitrogen fixation and related traits in a soybean recombinant inbred line population - C. Bennet Krueger; Jeffery D. Ray; James R. Smith; Arun Prabhu Dhanapal; Muhammad Arifuzzaman; Fei Gao; Felix B. Fritschi (Theoretical and Applied Genetics, 2024)

Evaluating the Development and Application of Stand Density Index for the Management of Complex and Adaptive Forests - Emmerson Chivhenge; David G. Ray; Aaron R. Weiskittel; Christopher W. Woodall; Anthony W. D’Amato (Current Forestry Reports, 2024)

Effect of dietary phytase on water and fecal prokaryotic and eukaryotic microbiomes in a hybrid tilapia (Oreochromis aureus x O. niloticus) mixotrophic biofloc production system - Candis L. Ray; Jason W. Abernathy; Bartholomew W. Green; Adam R. Rivers; Kevin K. Schrader; Steven D. Rawles; Matthew E. McEntire; Miles D. Lange; Carl D. Webster (Aquaculture, 2024)

Offsets in tide-gauge reference levels detected by satellite altimetry: ten case studies - R. D. Ray; M. J. Widlansky; A. S. Genz; P. R. Thompson (Journal of Geodesy, 2023)
Comparing measurements of absolute sea level by satellite altimetry and relative sea level by a tide gauge can reveal errors in either measurement system. Combining the measurements can determine vertical land motion (VLM) at the tide gauge. We here discuss ten case studies in which a tide gauge has likely experienced a small ( $$\le 10$$ ≤ 10 cm), discontinuous offset in the vertical, suggesting inadvertent loss of reference-level stability. Proper interpretation of offsets is helped if independent VLM measurements from nearby geodetic stations are available. In two cases, earthquake-induced VLM cannot be ruled out, although it appears unlikely. Offsets as small as 1–2 cm can be detected when both altimeter and tide gauge successfully observe the same ocean signal. This is most likely to occur for tide gauges located on small, open-ocean islands. Tide gauges near large land masses are typically more challenging owing to inadequacies of satellite altimetry near land and to differences between coastal and open-ocean sea levels. The case studies highlight the utility of satellite altimetry for tide-gauge quality control.

Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

Cytogenetic Diversity in Scilloideae (Asparagaceae): a Comprehensive Recollection and Exploration of Karyo-Evolutionary Trends - Sayantani Nath; Sayantika Sarkar; Sayali D. Patil; Partha Sarathi Saha; Manoj M. Lekhak; Sudipta Ray; Satyawada Rama Rao; S. R. Yadav; R. C. Verma; Manoj K. Dhar; S. N. Raina; Sumita Jha (The Botanical Review, 2023)

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

A GIS-based Spatial Prediction of Landslide Hazard Zones and Mapping in an Eastern Himalayan Hilly Region Using Large Scale Soil Mapping and Analytical Hierarchy Process - R. Srinivasan; D. Vasu; S. Amar Suputhra; Rajendra Hegde; S. K. Ray; S. K. Singh (Journal of the Indian Society of Remote Sensing, 2022)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Applications of Advanced Geospatial Technology for Expansion of Area under Horticultural Crops in North Eastern Region of India - B. K. Handique; C. Goswami; P. Jena; F. Dutta; R. Samiam; I. Nongrum; D. Jha; P. L. N. Raju; C. R. Deka; R. Sarma; K. Sarmah; H. K. Dutta; et al. (Journal of the Indian Society of Remote Sensing, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Large‐scale genome sampling reveals unique immunity and metabolic adaptations in bats - Diana D. Moreno Santillán; Tanya M. Lama; Yocelyn T. Gutierrez Guerrero; Alexis M. Brown; Paul Donat; Huabin Zhao; Stephen J. Rossiter; Laurel R. Yohe; Joshua H. Potter; Emma C. Teeling; Sonja C. Vernes; Kalina T. J. Davies; et al. (Molecular Ecology, 2021)
Comprising more than 1,400 species, bats possess adaptations unique among mammals including powered flight, unexpected longevity, and extraordinary immunity. Some of the molecular mechanisms underlying these unique adaptations includes DNA repair, metabolism and immunity. However, analyses have been limited to a few divergent lineages, reducing the scope of inferences on gene family evolution across the Order Chiroptera. We conducted an exhaustive comparative genomic study of 37 bat species, one generated in this study, encompassing a large number of lineages, with a particular emphasis on multi‐gene family evolution across immune and metabolic genes. In agreement with previous analyses, we found lineage‐specific expansions of the APOBEC3 and MHC‐I gene families, and loss of the proinflammatory PYHIN gene family. We inferred more than 1,000 gene losses unique to bats, including genes involved in the regulation of inflammasome pathways such as epithelial defence receptors, the natural killer gene complex and the interferon‐gamma induced pathway. Gene set enrichment analyses revealed genes lost in bats are involved in defence response against pathogen‐associated molecular patterns and damage‐associated molecular patterns. Gene family evolution and selection analyses indicate bats have evolved fundamental functional differences compared to other mammals in both innate and adaptive immune system, with the potential to enhance antiviral immune response while dampening inflammatory signalling. In addition, metabolic genes have experienced repeated expansions related to convergent shifts to plant‐based diets. Our analyses support the hypothesis that, in tandem with flight, ancestral bats had evolved a unique set of immune adaptations whose functional implications remain to be explored.

Breeding latitude is associated with the timing of nesting and migration around the annual calendar among Purple Martin (Progne subis) populations - L. R. Neufeld; S. Muthukumarana; J. D. Fischer; J. D. Ray; J. Siegrist; K. C. Fraser (Journal of Ornithology, 2021)

Removal of textile dyes from water by jute stick activated carbon: process optimization and isotherm studies - R. K. Ghosh; D. P. Ray; A. Tewari; I. Das (International Journal of Environmental Science and Technology, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Seasonal occurrence and sexual segregation of great white sharks Carcharodon carcharias in Mossel Bay, South Africa - Hannah R. Milankovic; Nicholas D. Ray; Louise K. Gentle; Christo Kruger; Esther Jacobs; Craig J. Ferreira (Environmental Biology of Fishes, 2021)
The seasonal occurrence and temporal sexual segregation of great white sharks Carcharodon carcharias have been widely documented in various temperate and sub-tropical waters across the globe. Yet, there is limited understanding of the relationship between the life stages and habitat use of C. carcharias , particularly in the Southern Cape. In this study, we investigated the population dynamics of C. carcharias in Mossel Bay, South Africa, between 2009 and 2013, using skipper logbooks and citizen research data obtained by a cage-diving vessel. A total of 3064 sharks, ranging in life history stages from young-of-the-year to subadult, were sighted during 573 trips. Juveniles dominated the sightings throughout the study, and there was marked sexual segregation, with females dominating the total sightings of sharks. C. carcharias were most abundant during the cooler, winter season, with females differing in abundance seasonally and males maintaining a low abundance throughout the year but peaking in the winter. In addition, sea surface temperature was the best indicator of C. carcharias presence. Abundance was greatest when vertical water visibility exceeded 3 m, with cloud cover influencing overall abundance negatively. Likely reasoning for the aggregation of C. carcharias in Mossel Bay includes the favourable conditions and abundance of food. Juvenile sharks may also utilise this area as a training ground to learn from larger conspecifics. This research demonstrates that information on population size and structure of C. carcharias can be obtained effectively through a compilation of logbook and citizen science data to assess and identify potential critical habitats in the quest to develop appropriate management strategies. This research also shows value in commercial cage-diving operations deriving international data sets needed to assess global populations of C. carcharias .

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

Mapping quantitative trait loci (QTL) for plant nitrogen isotope ratio (δ15N) in soybean - Sumandeep K. Bazzer; Jeffery D. Ray; James R. Smith; Felix B. Fritschi; Larry C. Purcell (Euphytica, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Identification of quantitative trait loci for carbon isotope ratio (δ13C) in a recombinant inbred population of soybean - Sumandeep K. Bazzer; Avjinder S. Kaler; Jeffery D. Ray; James R. Smith; Felix B. Fritschi; Larry C. Purcell (Theoretical and Applied Genetics, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Early life social and ecological determinants of global DNA methylation in wild spotted hyenas - Zachary M. Laubach; Christopher D. Faulk; Dana C. Dolinoy; Luke Montrose; Tamara R. Jones; Donna Ray; Malit O. Pioon; Kay E. Holekamp (Molecular Ecology, 2019)
Environmental factors early in life can have lasting influence on the development and phenotypes of animals, but the underlying molecular modifications remain poorly understood. We examined cross‐sectional associations among early life socioecological factors and global DNA methylation in 293 wild spotted hyenas ( Crocuta crocuta ) in the Masai Mara National Reserve, Kenya, grouped according to three age classes (cub, subadult and adult). Explanatory variables of interest included annual maternal rank based on outcomes of dyadic agonistic interactions, litter size, wild ungulate prey density and anthropogenic disturbance in the year each hyena was born based on counts of illegal livestock in the Reserve. The dependent variable of interest was global DNA methylation, assessed via the LUminometric Methylation Assay, which provides a percentage methylation value calculated at CCGG sites across the genome. Among cubs, we observed approximately 2.75% higher CCGG methylation in offspring born to high‐ than low‐ranking mothers. Among cubs and subadults, higher anthropogenic disturbance corresponded with greater %CCGG methylation. In both cubs and adults, we found an inverse association between prey density measured before a hyena was 3 months old and %CCGG methylation. Our results suggest that maternal rank, anthropogenic disturbance and prey availability early in life are associated with later life global DNA methylation. Future studies are required to understand the extent to which these DNA methylation patterns relate to adult phenotypes and fitness outcomes.

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Probing the effect of a room temperature ionic liquid on phospholipid membranes in multilamellar vesicles - S. Mitra; D. Ray; G. Bhattacharya; R. Gupta; D. Sen; V. K. Aswal; S. K. Ghosh (European Biophysics Journal, 2019)

Biogenic hydrogen sulphide emissions and non-sea sulfate aerosols over the Indian Sundarban mangrove forest - D. Ganguly; R. Ray; N. Majumdar; C. Chowdhury; T. K. Jana (Journal of Atmospheric Chemistry, 2018)

Association mapping identifies loci for canopy temperature under drought in diverse soybean genotypes - Avjinder S. Kaler; Jeffery D. Ray; William T. Schapaugh; Antonio R. Asebedo; C. Andy King; E. E. Gbur; Larry C. Purcell (Euphytica, 2018)

Transcriptomic changes in Echinochloa colona in response to treatment with the herbicide imazamox - Alice A. Wright; Rajkumar Sasidharan; Liisa Koski; Marianela Rodriguez-Carres; Daniel G. Peterson; Vijay K. Nandula; Jeffery D. Ray; Jason A. Bond; David R. Shaw (Planta, 2018)

Transcriptomic effects of adenosine 2A receptor deletion in healthy and endotoxemic murine myocardium - Kevin J. Ashton; Melissa E. Reichelt; S. Jamal Mustafa; Bunyen Teng; Catherine Ledent; Lea M. D. Delbridge; Polly A. Hofmann; R. Ray Morrison; John P. Headrick (Purinergic Signalling, 2017)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

A Novel Delivery System for the Root Symbiotic Fungus, Sebacina vermifera, and Consequent Biomass Enhancement of Low Lignin COMT Switchgrass Lines - Prasun Ray; Takako Ishiga; Stephen R. Decker; Geoffrey B. Turner; Kelly D. Craven (BioEnergy Research, 2015)

Equivalent Isopropanol Concentrations of Aromatic Amino Acids Interactions with Lipid Vesicles - Merrell A. Johnson; Bruce D. Ray; Stephen R. Wassall; Horia I. Petrache (The Journal of Membrane Biology, 2015)

Life at the leading edge: genetic impoverishment of the spotted bass, Micropterus punctulatus, at its Western edge - J. W. Ray; M. Husemann; D. J. Lutz-Carrillo; R. S. King; P. D. Danley (Environmental Biology of Fishes, 2015)

Erratum to: Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

Uromycladium falcatarium sp. nov., the cause of gall rust on Paraserianthes falcataria in south-east Asia - Chanintorn Doungsa-ard; Alistair R. McTaggart; Andrew D. W. Geering; Teresita U. Dalisay; Jane Ray; Roger G. Shivas (Australasian Plant Pathology, 2015)

Identification of a single gene for seed coat impermeability in soybean PI 594619 - Hirut Kebede; James R. Smith; Jeffery D. Ray (Theoretical and Applied Genetics, 2014)

Microbial Biomass Carbon Status in Agro-Ecological Sub Regions of Black Soils in India - Kulandaivelu Velmourougane; M. V. Venugopalan; T. Bhattacharyya; Dipak Sarkar; D. K. Pal; Apeksha Sahu; P. Chandran; S. K. Ray; Champa Mandal; K. M. Nair; Jagdish Prasad; R. S. Singh; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Secondary cell wall composition and candidate gene expression in developing willow (Salix purpurea) stems - Yongfang Wan; Cristina Gritsch; Theodora Tryfona; Mike J. Ray; Ambrose Andongabo; Keywan Hassani-Pak; Huw D. Jones; Paul Dupree; Angela Karp; Peter R. Shewry; Rowan A. C. Mitchell (Planta, 2014)

Developing Spectral Library of Major Plant Species of Western Himalayas Using Ground Observations - K. R. Manjunath; Amit Kumar; Mehra Meenakshi; R. Renu; S. K. Uniyal; R. D. Singh; P. S. Ahuja; S. S. Ray; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2014)

Urease Activity in Various Agro-ecological Sub-regions of Black Soil Regions of India - Kulandaivelu Velmourougane; M. V. Venugopalan; T. Bhattacharyya; Dipak Sarkar; D. K. Pal; Apeksha Sahu; P. Chandran; S. K. Ray; Champa Mandal; K. M. Nair; Jagdish Prasad; R. S. Singh; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Age and geochemistry of the Newania dolomite carbonatites, India: implications for the source of primary carbonatite magma - Jyotiranjan S. Ray; Kanchan Pande; Rajneesh Bhutani; Anil D. Shukla; Vinai K. Rai; Alok Kumar; Neeraj Awasthi; R. S. Smitha; Dipak K. Panda (Contributions to Mineralogy and Petrology, 2013)

TMEM43 mutations associated with arrhythmogenic right ventricular cardiomyopathy in non-Newfoundland populations - Berivan Baskin; Jon R. Skinner; Shubhayan Sanatani; Deborah Terespolsky; Andrew D. Krahn; Peter N. Ray; Stephen W. Scherer; Robert M. Hamilton (Human Genetics, 2013)

A new gene that controls seed coat wrinkling in soybean - Hirut Kebede; James R. Smith; Jeffery D. Ray (Euphytica, 2013)

Calibration of Ocean Wave Measurements by the TOPEX, Jason-1 , and Jason-2 Satellites - R. D. Ray; B. D. Beckley (Marine Geodesy, 2012)

Identification of a new soybean rust resistance gene in PI 567102B - Shuxian Li; James R. Smith; Jeffery D. Ray; Reid D. Frederick (Theoretical and Applied Genetics, 2012)

Genomic Location of a Gene Conditioning a Miniature Phenotype in Soybean [Glycine max (L.) Merr.] - Jeffery D. Ray; James R. Smith; Earl Taliercio; Felix B. Fritschi (Journal of Plant Biology, 2012)

Assessment of the Jason-2 Extension to the TOPEX/Poseidon, Jason-1 Sea-Surface Height Time Series for Global Mean Sea Level Monitoring - B. D. Beckley; N. P. Zelensky; S. A. Holmes; F. G. Lemoine; R. D. Ray; G. T. Mitchum; S. D. Desai; S. T. Brown (Marine Geodesy, 2010)

Respiratory muscle training reduces the work of breathing at depth - Andrew D. Ray; David R. Pendergast; Claes E. G. Lundgren (European Journal of Applied Physiology, 2010)

High-Oil Soybean for More Efficient Energy Conversion to Soy-Based Biodiesel - Robert L. Paris; Jeffery D. Ray; James R. Smith; Debbie L. Boykin (Natural Resources Research, 2009)

Genetics and mapping of adult plant rust resistance in soybean PI 587886 and PI 587880A - Jeffery D. Ray; Wilfrido Morel; James R. Smith; Reid D. Frederick; Monte R. Miles (Theoretical and Applied Genetics, 2009)

Characterization of the complete genome of influenza A (H5N1) virus isolated during the 2006 outbreak in poultry in India - Koninika Ray; Varsha A. Potdar; Sarah S. Cherian; Shailesh D. Pawar; Santosh M. Jadhav; Shamal R. Waregaonkar; Anshu A. Joshi; Akhilesh C. Mishra (Virus Genes, 2008)

In Vitro Characterization of a Compliant Biodegradable Scaffold with a Novel Bioreactor System - Antonio R. Webb; Bryan D. Macrie; Ananda S. Ray; Jack E. Russo; Andrew M. Siegel; Matthew R. Glucksberg; Guillermo A. Ameer (Annals of Biomedical Engineering, 2007)

Tidal analysis experiments with sun-synchronous satellite altimeter data - R. D. Ray (Journal of Geodesy, 2007)

Acetylcholinesterase activities in marine snail (Cronia contracta) as a biomarker of neurotoxic contaminants along the Goa coast, West coast of India - D. Gaitonde; A. Sarkar; S. Kaisary; C. D. Silva; C. Dias; D. P. Rao; D. Ray; R. Nagarajan; S. N. De Sousa; Subhodeep Sarker; D. Patill (Ecotoxicology, 2006)

Influence of menstrual cycle phase on pulmonary function in asthmatic athletes - Kristin I. Stanford; Timothy D. Mickleborough; Shahla Ray; Martin R. Lindley; David M. Koceja; Joel M. Stager (European Journal of Applied Physiology, 2006)

Reproductive history, occupational exposures, and thyroid cancer risk among women textile workers in Shanghai, China - E. Y. Wong; R. Ray; D. L. Gao; K. J. Wernli; W. Li; E. D. Fitzgibbons; Z. Feng; D. B. Thomas; H. Checkoway (International Archives of Occupational and Environmental Health, 2006)

The cystic fibrosis transmembrane conductance regulator gene and ion channel function in patients with idiopathic pancreatitis - Michele D. Bishop; Steven D. Freedman; Julian Zielenski; Najma Ahmed; Annie Dupuis; Sheelagh Martin; Lynda Ellis; Julie Shea; Isobel Hopper; Mary Corey; Paul Kortan; Gregory Haber; et al. (Human Genetics, 2005)

Colorectal Cancer Incidence Among Female Textile Workers in Shanghai, China: A Case-cohort Analysis of Occupational Exposures - A.J. De Roos; R. M. Ray; D. L. Gao; K. J. Wernli; E. D. Fitzgibbons; F. Ziding; G. Astrakianakis; D. B. Thomas; H. Checkoway (Cancer Causes & Control, 2005)

Molecular pathogenesis of Wilson disease: haplotype analysis, detection of prevalent mutations and genotype–phenotype correlation in Indian patients - A. Gupta; D. Aikath; R. Neogi; S. Datta; K. Basu; B. Maity; R. Trivedi; J. Ray; S. K. Das; P. K. Gangopadhyay; K. Ray (Human Genetics, 2005)

Low Levels of Nucleotide Diversity in Crocodylus moreletii and Evidence of Hybridization with C. acutus - David A. Ray; Jennifer A. Dever; Steven G. Platt; Thomas R. Rainwater; Adam G. Finger; Scott T. McMurry; Mark A. Batzer; Brady Barr; Peter J. Stafford; Jenna McKnight; Llewellyn D. Densmore (Conservation Genetics, 2004)

Short-arc analysis of intersatellite tracking data in a gravity mapping mission - D. D. Rowlands; R. D. Ray; D. S. Chinn; F. G. Lemoine (Journal of Geodesy, 2002)

Using GIS for siting artificial reefs—Data issues, problems and solutions: ‘Real World’ to ‘Real World’ - D. R. Green; S. T. Ray (Journal of Coastal Conservation, 2002)

The effect of vapor pressure deficit on maize transpiration response to a drying soil - Jeffery D. Ray; Russ W. Gesch; Thomas R. Sinclair; L. Hartwell Allen (Plant and Soil, 2002)

Short photoperiod inhibits winter growth of subtropical grasses - Thomas R. Sinclair; Paul Mislevy; Jeffery D. Ray (Planta, 2001)

Integrated commodity management methods with ca and/or fumigation - S. Prabhakaran; S. Ray; B. M. Schneider; R. E. Williams; P. Flinn; T. Phillips; D. Hagstrum; F. Arthur; J. Throne; R. N. Emery; R. A. Tassone; E. Kostas; et al. (Phytoparasitica, 2001)

Status of epidermal growth factor receptors family in hormone-dependent carcinomas of the breast and prostate with reference to serum lipids and lipoproteins - D. Jain; A. Ray; A. K. Bahadur; K. U. Chaturvedi; R. Sood; S. Sharma; S. L. D. Naik; B. K. Sharma (Indian Journal of Clinical Biochemistry, 2001)

A rare case of two malignancies: Carcinoma of the breast and uterine cervix - A. Ray; H. Mukundan; A. K. Bahadur; R. S. Rautela; S. L. D. Naik; B. K. Sharma (Indian Journal of Clinical Biochemistry, 2000)

Physico-Chemical Quality of Drinking Water in Rohtas District of Bihar - D. Ray; R. Ravindar Rao; A. V. Bhoi; A. K. Biswas; A. K. Ganguly; P. B. Sanyal (Environmental Monitoring and Assessment, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Angular momentum of Arctic Ocean tides - R. D. Ray; B. F. Chao; Z. Kowalik; A. Y. Proshutinsky (Journal of Geodesy, 1997)

Case 25 application of the concentration parameter of seismoactive faults to Southern California - A. Zavyalov; R. E. Habermann; A. D. Zavyalov; Ray E. Habermann; Paul Reasenberg; Chen Yong (Pure and Applied Geophysics, 1997)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)